Economic Reason: The Interplay of Individual Learning and External Structure - Clark, Andy (Academic Press, 1996)
Much work in economics, the social sciences, and elsewhere takes as it starting oint a somewhat unrealistic conception of rationality- a conception that ignores or downplays both the temporal and the situated aspects of human reason. Biological reason, I shall argue, is better concieved as an iterated process of adaptive response made under extreme time pressure and exquisitely keyed to a variety of external structures and circumstances.
Keywords: Philosophy